TeleCatch: manage and analyze telegram data - Ruscica, Giosue; Tucci, Giulia; Carneiro, Bia (2024)
TeleCatch is a comprehensive web application that provides a web-based interface and a REST api for managing and analyzing Telegram data. With a secure and user-friendly dashboard, users can manage Telegram accounts, configure data collections, and access insightful visualizations directly from their browser.